AB0042 Identification of Sulfido-Conjugated Mediators That Promote Resolution of Infection and Organ Protection. (15th July 2016) - Dalli, J.; Chiang, N.; Serhan, C.
Abstract : Background: When inflammation is self-limited it is host protective and leads to the repair and regeneration of damaged tissues. Chronic conditions, such as inflammatory arthritis, are though to arise from a failure of the host response to engage resolution mechanisms. The pro-resolving mechanisms engaged by the host response to promote tissue regeneration remain of interest. Objectives: In the present stud we aim to identify mediators produced during the resolution phase of acute inflammation, that promote the termination of the inflammatory response, tissue repair and regeneration. Methods: We employed LC-MS-MS and RP-UV-HPLC based lipid mediator metabolololipodomics to investigate novel bioactive molecules in isolates from mouse and human tissues and cells. Bioactions for identification and characterization of the novel molecules were determined using planaria, mice and human primary leukocytes. Results: Here we identified potent molecules present in infectious murine exudates, regenerating planaria, human milk as well as macrophages that stimulated tissue regeneration in planaria and are pro-resolving. Characterization of their physical properties and isotope tracking indicated that the bioactive structures contained sulfido-conjugated (SC) triene double bonds that proved to be 13-glutathionyl, 14-hydroxy-docosahexaenoic acid (SCI) and 13-cysteinylglycinyl, 14-hydroxy-docosahexaenoic acid (SCII). These molecules rescued E. coli infection-mediated delay in tissue regeneration in planaria, improving regeneration intervals from ∼4.2 to ∼3.7 days. Administration of SC protected mice from second organ injury and promoted repair via limiting neutrophil infiltration, upregulating Ki67 and Roof plate-specific spondin 3 in lung tissues. At nanomolar potencies these conjugates also resolved E. coli infections by limiting neutrophil infiltration, stimulating bacteria phagocytosis and clearance as well as efferocytosis of apoptotic cells. Conclusions: Together, these findings identify previously undescribed, conserved chemical signals and pathways in planaria, mice and human tissues that stimulate resolution of inflammation and promote the restoration of function. Acknowledgement: This work was supported in part by the National Institutes of Health (Grant P01GM095467). Disclosure of Interest: None declared